2017
DOI: 10.18805/ijare.a-4770
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of reference evapotranspiration using Aquacrop model for agro-climatic conditions of Madhya Pradesh

Abstract: Accurate estimation of evapotranspiration is necessary step for better management and allocation of water resources. The United Nations Food and Agriculture Organization (FAO) adopted the Penman Moneith method as a global standard to estimate reference crop evapotranspiration (ETo). The study aimed to estimate FAO P-M reference evapotranspiration for different district of five agro climatic zones of Madhya Pradesh state by using Aquacrop model. Daily weather data including maximum and minimum temperature, prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Hence the spatial variability of ET 0 is higher than the temporal variability indicating there is a higher variation of ET 0 in the space than in the years. The results obtained by (Yadav et al 2017) from Madhya Pradesh, India reveal that the lowest monthly sums of ET 0 is 76 mm and the highest value is 331 mm. The coe cient of variation ranged from 3-20 %, which is lower than temporal variability (except in August) indicating the differentiation of ET 0 values is more in the years than in the regions.…”
Section: Spatial Variability Of Etmentioning
confidence: 97%
See 2 more Smart Citations
“…Hence the spatial variability of ET 0 is higher than the temporal variability indicating there is a higher variation of ET 0 in the space than in the years. The results obtained by (Yadav et al 2017) from Madhya Pradesh, India reveal that the lowest monthly sums of ET 0 is 76 mm and the highest value is 331 mm. The coe cient of variation ranged from 3-20 %, which is lower than temporal variability (except in August) indicating the differentiation of ET 0 values is more in the years than in the regions.…”
Section: Spatial Variability Of Etmentioning
confidence: 97%
“…The coe cient of variation (CV) ranges from 9-37% for monthly sums in multi-year period in case of temporal variability analysis. Similar kind of investigation involving estimation of ET 0 using FAO P-M method and spatial and temporal analysis have been done by (Yadav et al 2017) using the daily climate data of 34 years for ve agro-climatic zones of Madhya Pradesh, India. The daily mean ET 0 varied from 4 mm − 10 mm/day which is higher than that of the ET 0 values obtained for the current study.…”
Section: Temporal Variability Of Etmentioning
confidence: 99%
See 1 more Smart Citation
“…The weighted average value of the chamber method evapotranspiration rate was 41.7% and 34.2% greater than the value of the Penman-Monteith evapotranspiration rate in the first and second period measurements. The smaller value for the Penman-Monteith method was due to the fact that this method only used global climate data and did not consider the position of land slopes in its measurement (Yadav et al, 2017). Results of research conducted by Manik et al, (2012); Prastowo et al, (2016);and Taolin et al (2017) at various locations showed that the average value of evapotranspiration rate calculated using Penman-Monteith method was 3 mm day -1 to 4.8 mm day -1 .…”
Section: Evapotranspiration Ratementioning
confidence: 99%